The case of the «Volga Espionage Organization». 1919 - A. V. Ganin (Омский научный вестник: Серия "Общество. История. Современность")
Based on unpublished sources from the Central Archive of the FSS of Russia, the article examines in detail the case of the counter-revolutionary «Volga Spy Organization» in the Red Army, investigated by the Cheka in 1919. This plot found a fragmentary reflection in historiography. The purpose of this work is to eliminate this gap. The theoretical basis of the study is a combination of the anthropological approach, problematic and biographical methods. As part of this case, along with other persons, several students of the Academy of the General Staff of the Red Army were arrested, who were suspected of a counter-revolutionary conspiracy. The course of the operational development of the case, the conduct of the investigation, the composition of the defendants (among them were the brothers Mikhail and Nikolai Tukhachevsky, who escaped arrest), were analyzed, the features of the sentences passed were discussed.